2018
DOI: 10.2147/ppa.s149355
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of medication adherence and responsible use of isotretinoin and contraception through Belgian community pharmacies by using pharmacy refill data

Abstract: PurposeThe aims of the study were to evaluate medication adherence and the influencing factors for isotretinoin and contraception (oral, patches, and rings) and to evaluate the concomitant use of contraception and isotretinoin.MethodsReimbursed prescription data from January 2012 to August 2015 of all patients in Belgium were received from Pharmanet–National Institute for Health and Disability Insurance. Medication adherence was measured according to the medication possession ratio. The influence of gender and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In Belgium, a recent retrospective study based on pharmacy refill data from January 2012 to August 2015 showed that only 15.6% of women aged between 12 and 21 years used an effective contraceptive method 1 month before, during and 1 month after isotretinoin treatment. This study also showed that the use of an effective contraceptive method is particularly not followed 1 month before treatment and at initiation …”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In Belgium, a recent retrospective study based on pharmacy refill data from January 2012 to August 2015 showed that only 15.6% of women aged between 12 and 21 years used an effective contraceptive method 1 month before, during and 1 month after isotretinoin treatment. This study also showed that the use of an effective contraceptive method is particularly not followed 1 month before treatment and at initiation …”
Section: Discussionmentioning
confidence: 71%
“…This study also showed that the use of an effective contraceptive method is particularly not followed 1 month before treatment and at initiation. 14…”
Section: Comparison With Literaturementioning
confidence: 99%
“…For instance, in Belgium, Biset et al conducted a study aimed at evaluating the concomitant use of contraception during Isotretinoin therapy. The study findings revealed that only a small proportion of studied women adhered to the use of contraception as recommended by the program ( Biset et al, 2018 ). A French study also assessed compliance with the PPP accompanied Isotretinoin use.…”
Section: Introductionmentioning
confidence: 97%
“…16,17 The consequences of low medication adherence to anti-acne treatment due to poor counseling and poor understanding of the proper use of the medicine result in additional unnecessary treatments, frustration, and increased medical expenses. 18 The pharmacists have to make sure that all instructions needed to use the medicine are clear. 16 In the United Arab Emirates (UAE), the medicines are classified as narcotics (only available in the hospitals), controlled or psychotropic drugs, semi-controlled drugs, POM, Pharmacist-only medicine, OTC, and GSL.…”
Section: Introductionmentioning
confidence: 99%